스마트 상호연결 이념을 토대로 한 민박 서비스 스마트화 디자인 연구 - 천추안완; Chenchuanwan; 이성필; Lee Sung Pil (기초조형학연구, 2020)
민박 서비스는 온라인 플랫폼과 여행시장을 기반으로 등장한 단기 임대 및 주거 서비스로, 중국의 부동산 임대 시장의 향후 10년간의 발전에 있어 매우 중요한 부분으로 작용하고 있다. 본 연구의 목적은 중국의 민박시장은 계속해서 확장되는 오늘날 여전히 고객에게 제공되는 인터렉티브 정보의 불균형 문제를 해결하기 위한 방안을 제시하는 데 있다. 이를 위해 중국의 대표적인 민박 서비스 온라인 플랫폼에서 제공되는 서비스의 현황을 살펴보고자 한다. 또한 선행연구를 통해 스마트 상호작용 기술을 이해하여 민박 서비스의 만족도를 확보할 수 있는 근거를 마련한다. 시장조사, 서비스 청사진, 원형 설계 등 방법을 통해 민박 서비스의 스마트화 설계를 개선할 수 있다. 이를 통해 스마트 상호연결이 적용된 민박 서비스에 존재하는 저효율, 단편적 체험, 획일화, 참신함 부족 등과 같은 문제점을 찾고, 3개의 스마트 상호연결이 적용된 민박 서비스 개선방법을 도출하여 민박 서비스에 존재하는 문제점들을 해결할 수 있다. 연구 결과를 통해 민박 서비스의 스마트 상호작용을 이루기 위해서는 무형의 서비스와 시스템뿐만 아니라 유형의 상품이 서로 상호작용하여 조화를 이룬 네트워크 상호연결이 구축되어야 함을 알 수 있다. 온라인 구매 사이트, 데이터, 클라우드 컴퓨팅 등 기술을 이용하면 이용자와 서비스 환경 간의 상호관계를 구축할 수 있어 서비스 상품과 환경이 소비자의 상황에 적합하게 조정됨으로써 소비자의 요구를 만족시킬 수 있다. 본 연구 결과가 스마트 상호작용이 적용된 중국의 민박 서비스의 만족도를 높이는 데 효과적인 근거가 되길 바라며, 또한 이후 스마트 상호연결이 적용된 글로벌 민박 서비스를 위한 참고자료가 되길 기대한다. Homestay, as short-term house tenancy relied on the internet platform and tourist market, will be a vital component of the Chinese house tenancy market over the next decade. This study is to provide solutions to the imbalance between continuous expansion of homestay market in China and the weakness of providing users interaction information of homestay. For this aspect, current service states of several representative homestay service information network platforms in China and foreign countries were analyzed. It also provides a basis for securing satisfaction of private lodging services by understanding smart interaction technologies through prior research. The design of homestay service experiences is optimized by market investigation, service blueprint and prototype design. On this basis, service shortages under the homestay service intelligence Internet mode were disclosed, including low efficiency, interrupted experiences, homogenization, lack of novelty, etc. Three solutions which implement the homestay service optimization based on the principle of intelligence Internet were proposed to solve existing problems in homestay services. Results show that it is necessary to set up intangible services and a system-tangible product interaction network, and establish user-service environment interactions using Things of Internet, big data and cloud end computing technologies to realize intelligent Internet of homestay services. These assure adaptation of service products and environment to user states, thus enabling to meet user demands. This study is expected to provide some design references to improve customer satisfaction to homestay services based on intelligence Internet.